2021
DOI: 10.1021/acs.jpclett.1c00418
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Luminescent Vapochromism of a Zero-Dimensional Sb3+-Doped Organic–Inorganic Hybrid

Abstract: Photoactive metal ions doping is an efficient way to modulate the photophysical properties of perovskite. Herein, we report a zero-dimensional (0D) InCl 6 (C 4 H 10 SN) 4 •Cl:Sb 3+ by doping Sb 3+ into InCl 6 (C 4 H 10 SN) 4 •Cl, which undergoes a significant enhancement of the emission peak at 550 nm with photoluminescence quantum yield boosting from 20% to 90%. Interestingly, a red-shifted emission is observed on InCl 6 (C 4 H 10 SN) 4 •Cl:Sb 3+ upon exposure to ethanol and DMF vapor with the emission peak r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 43 publications
7
74
0
Order By: Relevance
“…During the submission and revision process of this work, Sb 3+ -doped hydrated (C 8 NH 12 ) 6 InBr 9 ·H 2 O white-light emissive single crystals with a PLQY of 23.36% were reported independently, which feature the structure of isolated [InBr 6 ] 3− octahedra ( 14 ). Recently, Chen and coauthors reported 0D Sb 3+ -doped InCl 6 (C 4 H 10 SN) 4 ·Cl with isolated [InCl 6 ] 3− octahedra and displaying yellow emission ( 6 ), which exhibit reversible luminescent vapochromism to ethanol and N -dimethylformamide, and hence offer the opportunity of Sb 3+ -doped InCl 6 (C 4 H 10 SN) 4 ·Cl to serve as molecular sensors. Both of these works would promote the development of solid-state lighting technology and small-molecule sensors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the submission and revision process of this work, Sb 3+ -doped hydrated (C 8 NH 12 ) 6 InBr 9 ·H 2 O white-light emissive single crystals with a PLQY of 23.36% were reported independently, which feature the structure of isolated [InBr 6 ] 3− octahedra ( 14 ). Recently, Chen and coauthors reported 0D Sb 3+ -doped InCl 6 (C 4 H 10 SN) 4 ·Cl with isolated [InCl 6 ] 3− octahedra and displaying yellow emission ( 6 ), which exhibit reversible luminescent vapochromism to ethanol and N -dimethylformamide, and hence offer the opportunity of Sb 3+ -doped InCl 6 (C 4 H 10 SN) 4 ·Cl to serve as molecular sensors. Both of these works would promote the development of solid-state lighting technology and small-molecule sensors.…”
Section: Resultsmentioning
confidence: 99%
“…Three-dimensional (3D) organic-inorganic lead halide perovskites have gained tremendous attention due to their unique optical and electronic properties, such as high absorption coefficiency, easily tunable bandgaps, high charge carrier mobility, and exceptional defect tolerance, which further enable their successful implementation in solar cells, photodetectors, and light-emitting diodes (LEDs) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Very recently, low-dimensional lead halide perovskites have emerged as single-phase white-emitting materials due to their intriguing broadband emission behavior, which has been highlighted with excellent color stability and can efficiently avert self-absorption issues faced by the currently commercial multicomponent-based white-light sources (13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The large redshifted, broadband emission and the PL decay time on the order of microseconds are considered as the PL characteristics of self‐trapped excitons (STEs) or luminescence of ns 2 ‐metal ions. [ 31–36,42–47 ] It has been documented that In‐based halides without doping ns 2 ‐metal ions (Sb 3+ , Bi 3+ ) still have the large redshifted, broadband emission attributed to STEs. [ 31,44–49 ] After introducing ns 2 ‐metal ions, PL of the above In‐based halides only goes from weak to strong, not from nothing.…”
Section: Resultsmentioning
confidence: 99%
“…[ 31–36,42–47 ] It has been documented that In‐based halides without doping ns 2 ‐metal ions (Sb 3+ , Bi 3+ ) still have the large redshifted, broadband emission attributed to STEs. [ 31,44–49 ] After introducing ns 2 ‐metal ions, PL of the above In‐based halides only goes from weak to strong, not from nothing. Therefore, it may be not rigorous to use only one of the explanations.…”
Section: Resultsmentioning
confidence: 99%
“…This strategy is also reliable for low-dimensional metal halides, especially for the 0D metal halides [20,39]. Among the active ion doping procedures, Sb 3+ doping has been the most explored and effective approach to tune photoluminescence (PL) and enhance emission intensity [22,[40][41][42][43][44][45]. For instance, the PL intensity of Rb 2 InCl 5 (H 2 O) was relatively weak with a PL quantum yield (PLQY) of ~1.5%, but a dramatic enhancement was observed with the PLQY boosting to 90% upon Sb 3+ doping [43].…”
Section: Introductionmentioning
confidence: 99%